40.2k views
0 votes
(x3 + 1) is divided by (x2 – x + 1)?

User SynackSA
by
4.6k points

1 Answer

6 votes


x^3=x\cdot x^2, and
x(x^2-x+1)=x^3-x^2+x. Subtracting this from the dividend gives a remainder of


(x^3+1)-(x^3-x^2+x)=x^2-x+1


x^2=1\cdot x^2, and
1(x^2-x+1)=x^2-x+1. Subtracting this from the previous remainder gives a new one of


(x^2+x-1)-(x^2-x+1)=2x-2


x^2 does not divide
2x, so we're done, and we've found that


(x^3+1)/(x^2-x+1)=x+1+(2x-2)/(x^2-x+1)

i.e. you get a quotient of
x+1 and a remainder of
2x-2.

User James Joyce
by
5.1k points